Republic of Moldova : First Reviews Under the Extended Credit Facility and Extended Fund Facility Arrangements and Request for Modification of Performance Criteria-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report ;, 2017)
This paper discusses Moldova's First Reviews under the Extended Credit Facility and Extended Fund Facility Arrangements and Request for Modification of Performance Criteria. The program is broadly on track, enjoys strong country ownership, and is supported by policymakers' firm commitment to sound economic management. The authorities continue to make significant progress in tackling long-standing vulnerabilities in the financial sector and advancing structural reforms. These efforts have helped strengthen financial stability, and growth has resumed. The economy is projected to grow 4.5 percent in 2017, higher than previously expected. Continued steadfast program implementation is vital.